HTML5 game engines : app development and distribution - Nagle, Dan. (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"Build and Distribute Your Game Using an HTML5 Game EngineAs mobile hardware improves, HTML5 is gradually being used for gaming apps and a growing industry of game engines has begun to support it. HTML5 Game Engines: App Development and Distribution presents an introduction to development with HTML5 game engines as well as an in-depth look at popular engines. Along with downloadable example projects for each engine, the book provides techniques for packaging and distributing the final app to all the major platforms.Get Hands-On Guidance through Practical Techniques and ExamplesThe book is divided into three parts. The first one covers the essentials of HTML5, discusses development strategies and techniques, and takes you through a basic pong game running in the browser with no dependencies. The second part implements four games using the Crafty, EaselJS, Impact, and Turbulenz game engines. In the third part, the author describes how several of these games are distributed on platforms, such as the Chrome Web Store, Apple iOS App Store, Google Play Store, and Facebook"--
Includes bibliographical references (pages 185-192) and index.
Keywords: Computer games -- Programming; HTML (Document markup language); Internet games; Internet programming; Application software -- Development; COMPUTERS / Programming / Games